PENELITIAN KUALITAS AIR BENGAWAN SOLO PADA SAAT MUSIM KEMARAU - Rahayu, Sukmawati (JURNAL SUMBER DAYA AIR, 2018)
The Bengawan Solo which flows through Central and East Java is the largest river in Java Island, and its water is used for various activities such as agriculture, fishery, domestic use, irrigation, and water resources for drinking water. Based on a research carried out in upstream Bengawan Solo, water quality shows a decline indicated by the decrease of dissolved oxygen and increase of BOD and COD. At location Grogol, dissolved oxygen ranges between 4.4 – 7.9 mg/L and decreases at Kemiri to 0 – 6.4 mg/L. BOD at Grogol shows a range between 1.3 – 4.5 mg/L increasing to 4.8 – 8.1 mg/L at Kemiri. COD range between 3.7-13 mg/L at Grogol increases to 12 – 30 mg/L at Kemiri. In downstream Bengawan Solo, at location Napel and Babat, water quality indicates an increase indicated by increase of dissolved oxygen, and decrease ofBODand COD. The increasing dissolved oxygen and decreasingBODandCODin downstream area shows that the self purification process is happening in the river. The Fecal coli form bacteria at each location is found very high and beyond criteria.